ARAMEJSKIE SŁOWA I W YRAŻENIA W GRECE NOWEGO TESTAMENTU - Baranowski, Krzysztof (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2017)
In the New Testament, there are over thirty Aramaic words and phrases that are transcribed into Greek characters. Approximately half of them are personal and place names. Another half are individual words and four short phrases. This paper catalogues them and proposes Aramaic counterparts.